(untitled) (Cambridge, UK, 2003)
Problems are a central part of human life. The goal of The Psychology of Problem Solving is to organize in one volume what is known about problem solving and the factors that contribute to its success or failure. Unlike typical books on problem solving that are organized by content areas, such as mathematics and natural science, this book is organized by factors that affect problem solving performance, such as motivation, emotion, intellectual abilities, and working memory. The book constitutes the most thorough and up-to-date examination of problem solving currently available.
Keywords: Problem solving,Giải quyết vấn đề